Potassium Outflux and Distribution Density by the Sphericity Index in Erythrocytes Populations in Sodium Chloride Hypertonic Solutions - Alekseeva, L. I.; Kovalenko, S. E.; Kholodnyy, V. S.; Gordiyenko, O. I. (Problems of Cryobiology and Cryomedicine, 2005)
The authors studied the effect of human erythrocyte exposure time (from 30 s to 30 min) in sodium chloride hypertonic solution (0.4; 0.8; 1.2; 2.0 mol/l) on its distribution density by sphericity index in population and on potassium outflux of the cells. It was shown, that when exposing erythrocytes in hypertonic medium their state changed depending on exposure time and medium hypertonicity rate. Obtained peculiarities in erythrocyte state at various exposition terms in moderately hypertonic media (0.4-0.8 M NaCl) might be associated with spectrine cytomatrix and lateral re-distribution on membrane components in deformed membrane. In the case of cells’ exposition in more hypertonic solutions (1.2-2 M NaCl) the outflux of intracellular potassium became the main factor, affecting the erythrocyte distribution by sphericity index during their following placing into isotonic medium.